Night School: Jack Reacher #21 - Child, Lee (New York : Delacorte Press, 2016)
"In the morning, they gave Reacher a medal. That night, they sent him back to school. With eleven straight #1 New York Times bestsellers and over 100 million books sold, Jack Reacher is "the strongest brand in publishing" (Forbes Magazine). And Night School, with Reacher back in uniform, will be the biggest Reacher adventure of them all"--.
"In the morning, they gave Reacher a medal. That night, they sent him back to school. With eleven straight #1 New York Times bestsellers and over 100 million books sold, Jack Reacher is "the strongest brand in publishing" (Forbes Magazine). And Night School, with Reacher back in uniform, will be the biggest Reacher adventure of them all"--
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; FICTION / Suspense; FICTION / Thrillers; FICTION / Mystery & Detective / General; Suspense fiction; Mystery fiction